Giardiasis: A Review of Species, Clinical and Pathological Manifestation and Immunity - Abed, Zuhair Mohammed (American Journal of Biology and Natural Sciences, 2026)
Giardia are non-invasive intestinal protozoan parasites and are the causative agent of giardiasis. It is widely distributed worldwide, infecting humans, domestic animals such as cats and dog, as well as mammals, fish, and bird clinical signs range from asymptomatic infection to foul-smelling, fatty diarrhea, nausea, bloating, abdominal cramps and weight loss, and chronic exposure to the infection may lead to malabsorption. The Giardia duodenalis comprises genetically diverse variants categorized into assemblages A-H. Among these assemblages, assemblages A and B are of particular epidemiological importance due to their capacity to infect humans and animals.